Quality of medicines in resource-limited settings: need for ethical guidance. Issue 1 (1st January 2018) - Ravinetto, Raffaella; Pinxten, Wim; Rägo, Lembit
ABSTRACT: The quality of medicines is generally adequately assured by manufacturers and regulatory authorities for well-resourced settings, while the implementation of existing quality standards is challenged in many low- and middle-income countries. This situation of multiple pharmaceutical standards raises the question whether it could ever be ethically justified to compromise on the quality assurance of medicines depending on what individuals, communities, or societies can afford. In this paper, we contend that ethically, any unjustified exceptions to medicines' quality assurance represents a violation of the principles of beneficence and non-maleficence. Exceptions are only acceptable in exceptional and temporary circumstances, if based on a meaningful quality risk assessment, guided by a rigorous ethical framework built on the principles of independence, technical competence, transparency, and accountability. We also discuss how such exceptional and temporary circumstances should be defined/justified. Finally, we propose that empirical bioethics should acknowledge the existence of these dilemmas in public health, and help to build a normative approach to dealing with them. Ideally, an international group of experts in quality assurance/regulatory affairs and health ethicists should be set up to take up this topic and formulate a Guide to Ethical Principles of Quality Assurance of Medical Products.